2021
DOI: 10.1007/s00018-021-04002-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic endocannabinoids in obesity: an old story with new challenges

Abstract: The crucial role of the hypothalamus in the pathogenesis of obesity is widely recognized, while the precise molecular and cellular mechanisms involved are the focus of intense research. A disrupted endocannabinoid system, which critically modulates feeding and metabolic functions, through central and peripheral mechanisms, is a landmark indicator of obesity, as corroborated by investigations centered on the cannabinoid receptor CB1, considered to offer promise in terms of pharmacologically targeted treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 176 publications
(282 reference statements)
1
10
0
Order By: Relevance
“…Elevated hypothalamic endocannabinoid content has been associated with higher orexigenic signaling of ghrelin ( 123 125 ) and defective leptin signaling, observed in genetic models of obesity such as obese Zucker rats and db/db and ob/ob mice ( 126 , 127 ). These findings suggest that endocannabinoid mediators contribute to hyperphagia and obesity, which also supports the restorative effects of CBD treatment, once it reduces endocannabinoid signaling, especially through CB1 receptors ( 128 ). When it comes to inflammation, effects of CBD via CB2 receptor are more distinguished, since this receptor is more predominantly expressed on immune cells, including glial cells.…”
Section: Discussionsupporting
confidence: 62%
“…Elevated hypothalamic endocannabinoid content has been associated with higher orexigenic signaling of ghrelin ( 123 125 ) and defective leptin signaling, observed in genetic models of obesity such as obese Zucker rats and db/db and ob/ob mice ( 126 , 127 ). These findings suggest that endocannabinoid mediators contribute to hyperphagia and obesity, which also supports the restorative effects of CBD treatment, once it reduces endocannabinoid signaling, especially through CB1 receptors ( 128 ). When it comes to inflammation, effects of CBD via CB2 receptor are more distinguished, since this receptor is more predominantly expressed on immune cells, including glial cells.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, endocannabinoids, that are well known to stimulate feeding, activate POMC neurons leading to increased food intake via the release of the hunger promoting POMC-derived beta-endorphin and stimulation of downstream mu-opioid receptor (26). Interestingly, fasting (27) and cold exposure (28) are known to increase circulating and/or hypothalamic endocannabinoid levels to stimulate feeding and regulate energy metabolism flexibility (29). It is thus tempting to speculate that in conditions associated with increased endocannabinoid tone such as cold and fasting, endogenous ACBP may potentiate the release of beta-endorphin by POMC neurons, rather than alpha-MSH, to promote feeding.…”
Section: Results-discussionmentioning
confidence: 99%
“…CPT1C has been proposed to be a sensor of malonyl-CoA levels [ 8 , 28 , 48 ], and its role in the energy homeostasis and metabolic adaptation depends on this FA intermediary [ 27 , 49 ]. Recent investigations have found that malonyl-CoA binding provides CPT1C the potential to interact and regulate the activity of other downstream proteins such as ABHD6 [ 50 , 51 ] and SAC1 [ 52 ], both involved in brain metabolic flexibility, and AMPA-type glutamate receptors trafficking to the cell surface in neurons [ 52 ], whereas this regulation is lost in conditions of malonyl-CoA depletion [ 50 , 52 ]. CPT1C was also essential for neuronal activation evoked by ICV oleic acid, since the number of c-Fos-positive cells was not increased but reduced in PaV and VMH in CPT1C-KO exposed to oleic acid.…”
Section: Discussionmentioning
confidence: 99%